2010
DOI: 10.5604/20831862.907783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training time on serum immunoglobulin alterations and cortisol testosterone responses in male athlete students

Abstract: IntroductIonIt is necessary to pay attention to the important internal factors, biological clock, and the effect of such factors on physiological as well physical functions especially in different times of day and night.Recent evidences (knowing the effects of time on physiological variables) show that the human body undergoes a lot of changes during the day and the night, and has a special ability in each hour [1].Reilly et al. [11,12] showed that reaction time, muscular strength, anaerobic power, and the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The testosterone-to-cortisol ratio (T/C) is considered to be a sign of the hemostatic balance between both anabolic and catabolic states in athletes; and this ratio plays a significant role as a prognostic biological marker for insufficient recovery and overtraining syndrome 59 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The testosterone-to-cortisol ratio (T/C) is considered to be a sign of the hemostatic balance between both anabolic and catabolic states in athletes; and this ratio plays a significant role as a prognostic biological marker for insufficient recovery and overtraining syndrome 59 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the salivary IgA level may depend on both the intensity and duration of training as well as the type of physical activity [ 31 , 43 , 59 ]. On the other hand, there were no changes in the concentration of IgG, IgA, and IgM in serum of young men participating in a 16-week continuous running training [ 57 ].…”
Section: The Effect Of Physical Activity On the Salivary Iga Concentrmentioning
confidence: 99%
“…12 However, it is not in agreement with a study on the effects of training time on serum immunoglobulin in male athlete students, which showed that there were not any significant differences between the amounts of serum immunoglobulins of both groups in pre-test and post-test. 10 Generally in exercise immunology, an increase in immunoglobulin concentration has usually been interpreted to represent enhanced immunity, and a decrease is usually interpreted as immunosuppression. The alteration in the concentration of IgM, the first antibody (immunoglobulin) class produced in an immune response, as well as that of IgG, in both moderate and vigorous exercise groups, could be as a result of the antigen stimulation through greater-than-normal quantities of microorganisms especially airborne microbes entering the body through both increased ventilation rates or increased lungs ventilation and breakdown of natural mucosal immunity by drying of airway secretions, during the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…7 A study on the effects of training time on serum immunoglobulin alterations, cortisol, and testosterone responses in male athlete students, showed that there were not any significant differences between the amounts of serum immunoglobulins of both groups in pre-test and post-test. 10 Also, another study on the influence of ultra-endurance exercise on immunoglobulin isotypes and subclasses reported that the serum immunoglobulins were significantly altered after the race. 11 Moreover, a study on the influence of selected exercise on serum immunoglobulins A, M and G in semiendurance elite runners reported that long and intensive exercises weaken the immune system, while moderate and short drills strengthened this system.…”
mentioning
confidence: 99%